2012
DOI: 10.1001/archinternmed.2011.732
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution and the Risk of Acute Ischemic Stroke

Abstract: Background The link between daily changes in ambient fine particulate matter air pollution (PM2.5) and cardiovascular morbidity and mortality is well established. Whether PM2.5 at levels below current US National Ambient Air Quality Standards also increases the risk of ischemic stroke remains uncertain. Methods We reviewed the medical records of 1705 Boston-area patients hospitalized with neurologist-confirmed ischemic stroke and abstracted data on the time of symptom onset and clinical characteristics. PM2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
251
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(270 citation statements)
references
References 44 publications
12
251
4
3
Order By: Relevance
“…Few studies have examined health outcomes in association with exposure levels defined by the AQI. One recent study found that exposure to PM 2.5 in the "moderate" range of the AQI (previously defined as 15-40 mg/m 3 ) was associated with increased risk of acute ischemic stroke (30).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined health outcomes in association with exposure levels defined by the AQI. One recent study found that exposure to PM 2.5 in the "moderate" range of the AQI (previously defined as 15-40 mg/m 3 ) was associated with increased risk of acute ischemic stroke (30).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies conducted in the Boston area have reported positive associations of short‐term exposure to air pollution with acute stroke onset,28 atrial fibrillation,29 and myocardial infarction onset 30. In the present study, we evaluated whether short‐term (1–7 days) ambient air pollution exposure is associated with systemic levels of oxidative stress, measured by plasma myeloperoxidase and urinary creatinine‐indexed 8‐epi‐PGF 2α , in the community‐based Framingham Heart Study.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified 18 studies, which fulfilled these criteria (Table 4). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] ACUTE EFFECTS OF PARTICULATE MATTER EXPOSURE Although most studies on PM and cardiovascular diseases have been conducted in developed western countries, first impulses for epidemiologic research on IS came from South Korea and Taiwan. 15,22,25 An increase in PM by an interquartile range in Seoul was associated with a 3% higher IS mortality.…”
Section: Particulate Matter and Human Health Particulate Matter Is Amentioning
confidence: 99%
“…20,27,28 Only three results reached the level of significance. 14,16,25 This reveals limitations of comparing air pollution and its influence on health outcomes globally. The composition of PM varies dramatically dependent on pollution sources like car traffic or industry.…”
Section: Particulate Matter and Human Health Particulate Matter Is Amentioning
confidence: 99%
See 1 more Smart Citation